Encyclopedia of government and politics. V.2 (London ; New York : Routledge, 1992)
This book is about: Political theory: central concepts; Contemporary ideologies; Contemporary political systems; Political institutions; Political forces and political processes; Centripetal and centrifugal forces in the nation-state; ...
Keywords: Political science; Encyclopedias; Political science -- Encyclopedias